Konsep Dasar dan Perencanaan Evaluasi Program Pendidikan - Fadhilah Rahmafitri; Elvi Deswita; Jumadil Ranto Mulia; Zulmuqim (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The evaluation of educational programs is an essential process that not only assesses the success of learning but also evaluates the implementation of core values that form the foundation of education. In the realm of education, program evaluation aids in measuring the effectiveness of a program, identifying areas that require improvement, and ensuring the successful attainment of educational objectives. This article explicates the fundamental concept of program evaluation, encompassing its definition, objectives, scope, and planning. Program evaluation is not a one-time process but rather a series of measurements with specific goals. The research method employed is the library research method, which involves a literature review approach, examining relevant sources or references pertaining to the research issue to seek answers. The findings of this research present various definitions and objectives of program evaluation along with the designs, information, samples, and costs involved in its planning. The article highlights the significance of comprehending key elements that construct an effective and sustainable educational program, emphasizing the pivotal role of evaluation planning in ensuring the success of educational programs aligned with their objectives.